Derivative hydrogen production method in fused quartz femtosecond laser processing / welding process
By introducing atomic defects and Si-OH groups on the surface of fused quartz glass, hydrogen is generated by femtosecond laser processing/welding reaction, the existing green hydrogen technology is solved, and the problems of poor economics and carbon dioxide emissions are achieved, and efficient and environmentally friendly hydrogen is achieved Production.
Patent Information
- Application Number
- CN202411403103.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2024-12-27
AI Technical Summary
The existing green hydrogen hydrogen production technology is poor in economics, cannot be used on a large scale, and has carbon dioxide emission problems, so new hydrogen production methods are urgently needed.
By femtosecond laser processing/welding of the surface of the fused quartz glass after washing, ALD coating is used to introduce atomic defects and Si-OH groups, combined with femtosecond laser, the decomposition reaction is combined with the action of femtosecond laser to generate hydrogen, and high vacuum and ultrapure water conditions are used to perform Hydrogen gas collection.
It achieves clean and efficient hydrogen generation without catalysts and does not generate carbon dioxide emissions, which has important technical guidance significance.
Smart Images

Figure CN119191685A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of fused quartz femtosecond laser processing, and in particular relates to a hydrogen production method derived from femtosecond laser processing / welding of a washed fused quartz glass surface. Background Art
[0002] In today's society, with the increasing development of industry and technology, there is a huge demand for energy. The excessive use of fossil fuels has caused serious ecological and environmental problems and energy crisis. It is of great significance to store and utilize a new energy source on a large scale to replace fossil energy.
[0003] Hydrogen has the characteristics of high energy density and pollution-free combustion, and is a widely used energy carrier. At present, hydrogen energy technology routes are mainly divided into three types: gray hydrogen, blue hydrogen and green hydrogen. Gray hydrogen and blue hydrogen are the main means, but they still emit a large amount of carbon dioxide; green hydrogen refers to hydrogen produced by water decomposition reaction using renewable energy, which is the most ideal source of hydrogen energy. Large-scale use of renewable energy water to prepare "green hydrogen" is an important guarantee for achieving the "dual carbon" goal and even building a sustainable society. However, the development of green hydrogen technology is still limited. The technical and economic efficiency of green hydrogen production is poor, and the main means is still through water electrolysis. The cost is high and cannot be applied on a large scale in industry. There is an urgent need to seek new ideas and methods for hydrogen production. Summary of the invention
[0004] In view of the shortcomings of the above-mentioned existing hydrogen production technology, the present invention provides a method for producing hydrogen by femtosecond laser processing / welding the surface of fused quartz glass after water washing. By introducing atomic-level defects by ALD coating, a large amount of Si-OH and interstitial water molecules will be generated during the water washing process. The Si-OH group will decompose into NBOHC defects and excited H during the femtosecond laser processing / welding process, and the interstitial water molecules will also decompose into excited H and -OH during the femtosecond laser processing / welding process. Excited H can easily react to generate H2. Si-OH will also react with Si-H to generate a conventional Si-O-Si structure and hydrogen. In addition, water molecules will react with oxygen vacancy defects in the fused quartz, and O atoms will produce hydrogen in the process of bridging the defects.
[0005] The technical solution of the present invention is:
[0006] A hydrogen production method derived from the process of fused quartz femtosecond laser processing / welding, the method comprising: using femtosecond laser processing and water-washed coated fused quartz glass to produce hydrogen.
[0007] In the hydrogen production method of the present invention, one aspect that needs to be noted is that a homogeneous SiO2 film can be added to the surface of the fused silica glass in advance by atomic layer deposition (ALD) coating. The purpose is to introduce atomic level defects, including but not limited to vacancy defects, five-membered Si rings and four-membered Si rings; so that a large number of silanol groups (Si-OH) are generated during the water washing process, which serve as key reactants to generate H2 during femtosecond laser processing / welding.
[0008] Another thing to note is that the wavelength of the femtosecond laser is 800nm, the pulse width is 100fs, and the repetition frequency is 1000Hz. When producing hydrogen, its energy density should be higher than 4.13J / cm 2 .
[0009] In order to obtain a better hydrogen production effect, the specific femtosecond laser process parameters should be adjusted according to the actual laser parameters and fused quartz.
[0010] A method for producing hydrogen derived from a fused quartz femtosecond laser processing / welding process comprises the following steps:
[0011] Step 1: using the ALD coating method to deposit a layer of SiO2 film on the surface of fused quartz;
[0012] Step 2, ultrasonically cleaning the deposited fused quartz glass;
[0013] Step 3, rinsing the cleaned fused quartz glass;
[0014] Step 4, allowing the rinsed fused quartz glass to dry naturally;
[0015] Step 5, determining the process parameters of the femtosecond laser processing / welding process;
[0016] Step 6: Adjust the position of the three-dimensional processing platform to determine the posture of the fused quartz glass sheet and the laser scanning path;
[0017] Step 7: Place the dried fused quartz glass into the vacuum chamber and fix it with a clamp. Connect the vacuum chamber valve to the vacuum pump;
[0018] Step 8: Connect the vacuum chamber valve to the vacuum pump and pump air until the pressure gauge reaches the high vacuum requirement, then close the valve;
[0019] Step 9, performing femtosecond laser scanning on the fused quartz surface;
[0020] Step 10: After processing / welding is completed, open the vacuum chamber valve to collect hydrogen.
[0021] Furthermore, the ALD coating method used in step 1 is to deposit a homogeneous SiO2 film on the surface of fused quartz. The Si source used is bis(tert-butylamino)silane (BTBAS), the O source used is ozone molecules, and the film thickness is 200nm-800nm.
[0022] Furthermore, the ultrasonic cleaning in step 2 requires that the fused quartz be placed vertically on a rack, and the rack be placed in a glass dish. Ultrapure water is injected to cover the fused quartz glass, and then placed in an ultrasonic cleaning machine. The fused quartz is cleaned in water at different ultrasonic frequencies, and the ultrapure water in the glass dish needs to be replaced after each cleaning.
[0023] Furthermore, the water used for rinsing in step 3 should be ultrapure water.
[0024] Furthermore, the natural drying in step 4 should be carried out in an ultra-clean environment with a temperature maintained at 25°C.
[0025] Furthermore, step 5 determines the laser parameters used in the femtosecond laser processing / welding process, and the laser parameters include femtosecond laser pulse width, wavelength, power, and repetition frequency.
[0026] Furthermore, in step 6, the focus of the femtosecond laser is placed on the front surface of the fused quartz by a beam analyzer, and the moving path of the three-dimensional motion platform is determined by the starting position and the ending position of the laser processing / welding.
[0027] Furthermore, the two ends of the vacuum chamber used in step 7 are glass lenses, and a valve is provided on the vacuum chamber for exhausting and inletting air.
[0028] Furthermore, the vacuum degree required for the exhaust in step 8 is high vacuum degree, that is, the pressure P<10 -1 ~10 -5 Pa.
[0029] Furthermore, when the fused silica glass is processed / welded in step 9, the scanning paths used include but are not limited to raster-type, concentric circle-type, concentric rectangular-type and other paths.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] The present invention proposes a new idea for hydrogen production. On the one hand, a large number of atomic defects are introduced by ALD coating, and the source of Si-OH is increased. On the other hand, four hydrogen source pathways are proposed through the reaction process of SiOH, interstitial water molecules, Si-OH and atomic defects under the action of femtosecond laser. This method is clean, simple, efficient, and does not require the participation of catalysts; hydrogen is produced through renewable water energy and continuously reused fused quartz glass, and no carbon dioxide emissions are generated during the reaction process, which has important guiding significance for the development of new laser hydrogen production technologies. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a physical picture of ultrasonic cleaning of fused quartz glass in step 2 in an embodiment of the present invention.
[0033] Figure 2 Detailed description of the invention FIG. 1 is a physical diagram of the vacuum chamber used in step 7 in an embodiment of the present invention.
[0034] Figure 3 Schematic diagram of the raster path for performing femtosecond laser scanning in step 9 in an embodiment of the present invention.
[0035] Figure 4 This is a reaction model between a fused quartz system containing oxygen vacancy defects and water molecules calculated using Lammps molecular dynamics software in an embodiment of the present invention.
[0036] Figure 5 1 is the photoluminescence spectrum result of the fused silica glass before and after femtosecond laser processing in the embodiment of the present invention.
[0037] Figure 6 Graph showing hydrogen yield in an embodiment of the present invention. DETAILED DESCRIPTION
[0038] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.
[0039] A method for producing hydrogen derived from a fused quartz femtosecond laser processing / welding process comprises the following steps:
[0040] Step 1: using the ALD coating method to deposit a layer of SiO2 film on the surface of fused quartz;
[0041] The size of the fused quartz glass used is 50mm×50mm×5mm. The ALD coating process is to coat a 300nm SiO2 film on the surface of the fused quartz at a temperature of 350°C. The Si source used is bis(tert-butylamino)silane (BTBAS), and the O source used is ozone molecules.
[0042] Step 2, ultrasonically cleaning the deposited fused quartz glass;
[0043] like Figure 1 As shown, place the fused quartz vertically on a PTFE rack, and place the rack in a glass dish. Pour ultrapure water with a resistance of more than 18MΩ into the culture dish until the fused quartz glass is completely covered. The ultrasonic cleaning machine is heated to 40°C, and the ultrasonic cleaning is performed at 25KHz, 35KHz, 45Khz, and 135KHz for 15 minutes. The ultrapure water in the glass dish needs to be replaced after each cleaning.
[0044] Step 3, rinsing the cleaned fused quartz glass;
[0045] The six surfaces of the fused quartz glass were rinsed separately using a pulsed ultrapure water nozzle, and the rinsing time for each surface was 3 minutes.
[0046] Step 4, allowing the rinsed fused quartz glass to dry naturally;
[0047] The fused quartz glass was placed in an ultra-clean environment at 25°C to dry naturally for 12 hours, at which time no water remained on the surface.
[0048] Step 5, determining the process parameters of the femtosecond laser processing / welding process;
[0049] The process parameters of femtosecond laser processing are set as follows: femtosecond laser pulse width is 100 fs; repetition frequency is 1000 Hz, average power is 300 mW, and wavelength is 800 nm.
[0050] Step 6: Adjust the position of the three-dimensional processing platform to determine the posture of the fused quartz glass sheet and the laser scanning path;
[0051] The focus of the femtosecond laser is placed on the front surface of the fused quartz through a beam analyzer, and the spot size is 43um. The moving path scanning speed of the three-dimensional motion platform is determined to be 10mm / s and the spot overlap is 1 / 4 of the spot diameter through the starting and ending positions of the laser processing / welding.
[0052] Step 7: Place the dried fused quartz glass into the vacuum chamber and fix it with a clamp. Connect the vacuum chamber valve to the vacuum pump;
[0053] like Figure 2 As shown, there are glass lenses at both ends of the vacuum chamber, and two valves are provided on the vacuum chamber for exhaust and intake. The fixture is located in the middle of the vacuum chamber, and the ALD coating surface faces the femtosecond laser light outlet.
[0054] Step 8: Connect the vacuum chamber valve to the vacuum pump and pump air until the pressure gauge reaches the high vacuum requirement, then close the valve;
[0055] When the pressure in the vacuum chamber reaches 10 -1 When 0.04 Pa, turn off the vacuum pump and close the valve.
[0056] Step 9, performing femtosecond laser scanning on the fused quartz surface;
[0057] like Figure 3 As shown, a 40mm×40mm raster scanning path is achieved by a three-dimensional mobile platform.
[0058] Step 10: After processing / welding is completed, open the vacuum chamber valve to collect hydrogen.
[0059] After femtosecond laser processing is completed, an air bag is used to connect the vacuum chamber valve to collect hydrogen.
[0060] The mechanism of the present invention utilizes the following four reaction pathways:
[0061] 1.H2O+≡Si Si≡(oxygen vacancy)→Si-O-Si+H2
[0062] 2.H2O+fs→H2O*→H*+OH*; H*+H*→H2
[0063] 3.SiOH+fs→Si-O.(NBOHC)+H*; H*+H*→H2
[0064] 4.≡SiOH+≡SiH→≡Si-O-Si≡+H2
[0065] (*refers to excited state / unstable state)
[0066] Among them, path 1 can be calculated by molecular dynamics software lammps based on ReaxFF reaction force field, such as Figure 4 As shown, water molecules were randomly added to the system containing oxygen vacancy defects, and the O atoms in the water molecules produced hydrogen in the process of bridging the oxygen vacancy defects.
[0067] Path 2 describes the interstitial water molecules in fused silica glass, which can generate excited H atoms under the action of femtosecond laser. Two excited H atoms can directly generate H2.
[0068] Path 3 describes that water molecules will react with fused silica glass to produce a large amount of Si-OH. This is because in the fused silica system, the activation energy corresponding to the six-membered ring is 0.8–0.9eV, the five-membered ring is 1.8eV, and the four-membered ring is 2.0-2.2eV. The reaction barrier of H2O+SiO2→2SiOH is only 1.5eV, so at low temperatures, when a water molecule enters a five-membered ring or narrower ring, it will react with the network. If this process takes long enough to reach equilibrium, then due to the low formation energy of Si-OH (0.3-0.7eV), their number will be quite large. Si-OH will decompose during femtosecond laser processing / welding to produce NBOHC defects and excited H atoms. Figure 5 As shown in the figure, when the processed fused quartz was tested for fluorescence spectrum, the fluorescence intensity of the NBOHC defect represented by the 652nm peak increased dramatically, which also indicates that a large number of excited H atoms will be generated in the system. It is the main source of H2
[0069] The Si-H described in Path 4 is obtained by the reaction of the fused quartz atomic defect "≡Si" and the excited H atom, and the reaction of Si-OH and Si-H is also accompanied by the generation of H2
[0070] In order to verify the accuracy of the interpretation method of the present invention, a gas chromatograph can be used for verification.
[0071] The hydrogen yield is Figure 6 As shown in the figure, with the increase of energy density during femtosecond laser processing / welding, the hydrogen production rate gradually increases.
[0072] Although the present invention is disclosed as above, the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Technicians in the field of the present invention can make various changes and modifications without departing from the spirit and scope of the present invention, and these changes and modifications will fall within the protection scope of the present invention.
Claims
1. A method for producing hydrogen derived from fused silica femtosecond laser processing / welding, characterized in that: The method comprises the following steps: using femtosecond laser to process and wash the coated fused quartz glass to prepare hydrogen.
2. The method for producing hydrogen derived from the fused silica femtosecond laser processing / welding process according to claim 1, characterized in that: A layer of homogeneous SiO2 film is added on the surface of fused quartz glass by atomic layer deposition (ALD) coating.
3. The method for producing hydrogen derived from the fused silica femtosecond laser processing / welding process according to claim 1, characterized in that: The wavelength of femtosecond laser is 800nm, the pulse width is 100fs, the repetition frequency is 1000Hz, and its energy density should be higher than 4.13J / cm when producing hydrogen. 2 .
4. A method for producing hydrogen derived from fused silica femtosecond laser processing / welding, characterized in that: The following steps are involved: Step 1: Depositing a homogeneous SiO2 film on the surface of fused quartz by ALD coating method; Step 2, ultrasonically cleaning the deposited fused quartz glass; Step 3, rinsing the cleaned fused quartz glass; Step 4, allowing the rinsed fused quartz glass to dry naturally; Step 5, determining the process parameters of the femtosecond laser processing / welding process; Step 6: Adjust the position of the three-dimensional processing platform to determine the posture of the fused quartz glass sheet and the laser scanning path; Step 7: Place the dried fused quartz glass into a vacuum chamber and fix it with a clamp; connect the vacuum chamber valve to a vacuum pump; Step 8: Connect the vacuum chamber valve to the vacuum pump and pump air until the pressure gauge reaches the high vacuum requirement, then close the valve; Step 9, performing femtosecond laser scanning on the fused quartz surface; Step 10: After processing / welding is completed, open the vacuum chamber valve to collect hydrogen.
5. The method according to claim 4, characterized in that The ALD coating method used in step 1 is to deposit a homogeneous SiO2 film on the surface of fused quartz. The Si source used is bis(tert-butylamino)silane, the O source used is ozone molecules, and the film thickness is 200nm-800nm.
6. The method according to claim 4, characterized in that The ultrasonic cleaning in step 2 requires that the fused quartz be placed vertically on a rack, and the rack be placed in a glass dish; ultrapure water is injected to cover the fused quartz glass, and then placed in an ultrasonic cleaning machine; and water-insulated cleaning is performed at different ultrasonic frequencies. After each cleaning, the ultrapure water in the glass dish needs to be replaced.
7. The method according to claim 4, characterized in that The water used for rinsing in step 3 should be ultrapure water.
8. The method according to claim 4, characterized in that The natural drying in step 4 should be carried out in an ultra-clean environment with a temperature maintained at 25°C.
9. The method according to claim 4, characterized in that Step 5 determines the laser parameters used in the femtosecond laser processing / welding process, wherein the laser parameters include femtosecond laser pulse width, wavelength, power, and repetition frequency.
10. The method according to claim 4, characterized in that Step 6: The focus of the femtosecond laser is placed on the front surface of the fused quartz by a beam analyzer, and the moving path of the three-dimensional motion platform is determined by the starting position and the ending position of the laser processing / welding; The vacuum chamber used in step 7 has glass lenses at both ends, and a valve is provided on the vacuum chamber for exhausting and inletting air; The vacuum degree required for the exhaust in step 8 is high vacuum, that is, the pressure P<10 -1 ~10 -5 Pa; When the fused silica glass is processed / welded in step 9, the scanning paths used include but are not limited to raster-type, concentric circle-type, and concentric rectangular paths.
